OPTIMALISASI PROSES SELEKSI HAKIM MAHKAMAH KONSTITUSI TERHADAP INTEGRITAS PUTUSAN BERKEADILAN - Taufik, Muh Bambang; Sofyan, Sofyan; Al Haditzy, Ihzurt; Sulfianah; Aulia, Zuriatul (Qaumiyyah: Jurnal Hukum Tata Negara, 2024)
In an era of dynamic legal development, this research aims to optimize the selection process of Constitutional Court judges in order to improve the integrity of just decisions. The background of this research is based on the need for a transparent and trustworthy judicial system for the community. This need arises from concerns about fraud and manipulation in the judicial process that can undermine public confidence in the legal system. The accuracy of the use of research approaches and methods plays an important role in this research, so this research uses a quantitative approach with a literature study method, namely by analyzing data from various sources such as relevant books or journals. The results show that the selection process of Constitutional Court judges still needs to be improved to ensure the integrity of the decisions produced. This improvement is important to ensure the sustainability of the Indonesian legal system and the integrity of decisions in accordance with the law and state administration. Clear and standardized selection process reforms and effective oversight are needed to improve the quality of constitutional judges and ensure high decision integrity. In conclusion, there is a need to increase transparency and accountability in the selection process of Constitutional Court judges in order to create more equitable justice that is recognized by the community. The implication of the results of this study is the need for reform in the judge selection system to ensure the upholding of the rule of law and public trust in the judiciary. Abstrak Pada era perkembangan hukum yang dinamis, penelitian ini bertujuan untuk mengoptimalkan proses seleksi hakim Mahkamah Konstitusi guna meningkatkan integritas putusan yang berkeadilan. Latar belakang penelitian ini berdasarkan pada kebutuhan akan sistem peradilan yang transparan dan dapat dipercaya bagi masyarakat. Kebutuhan ini timbul dari kekhawatiran akan kecurangan dan manipulasi dalam proses peradilan yang dapat merusak kepercayaan masyarakat terhadap sistem hukum. Ketepatan penggunaan pendekatan dan metode penelitian berperan penting dalam penelitian ini, sehingga penelitian ini menggunakan pendekatan kuantitatif dengan metode studi pustaka yakni dengan analisis data dari berbagai sumber seperti buku atau jurnal yang relevan. Hasil penelitian menunjukkan bahwa proses seleksi hakim Mahkamah Konstitusi masih perlu diperbaiki guna memastikan integritas putusan yang dihasilkan. Perbaikan ini penting untuk memastikan keberlangsungan sistem hukum Indonesia dan integritas putusan yang sesuai dengan hukum dan ketatanegaraan. Reformasi proses seleksi yang jelas dan baku serta pengawasan yang efektif diperlukan untuk meningkatkan kualitas hakim konstitusi dan memastikan integritas putusan yang tinggi. Sebagai kesimpulan, perlu adanya peningkatan transparansi dan akuntabilitas dalam proses seleksi hakim Mahkamah Konstitusi agar mampu menciptakan keadilan yang lebih merata dan diakui oleh masyarakat. Implikasi dari hasil penelitian ini adalah perlunya reformasi dalam sistem seleksi hakim guna memastikan tegaknya supremasi hukum dan kepercayaan publik terhadap lembaga peradilan.